Use of Mobile Phones Among Prospective Pastors Helps in Carrying Out Daily Routines - Benedictus Adiatma Murti Wibowo; Agustinus Tri Edi Wasono; Yohanes Subali (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Communication and information technology is experiencing rapid development. This development can be seen from the means of communication, namely mobile phones. Mobile is a portable tool because it can be used to communicate, but also to gather information and is practical to carry anywhere. Through cell phones, it is quite easy for the public to access news and information that has happened and is happening. This convenience is also experienced in the education or training of prospective priests (seminaries). The educational process for the formation of prospective priests (brothers) has had an impact or influence on the development of information technology in the world. This research is to see the use of mobile phones among prospective priests which helps in carrying out daily routines. In this study, the author will conduct interviews with 5 seminarians of St. Paul's Major Seminary, Yogyakarta. The five brothers are students currently undergoing a master's program at Santa Dharma University. The purpose of this study was to find out the use of cell phones as a means of technological progress that helps the brothers carry out their daily routines. In addition, mobile phones are also a means of gathering information related to pastoral learning and services.